Heterosubstitution Reaction on Coordinated Bivalent Quadridentate Ligands of Nickel(II) and Copper(II) - Balsubhramanian, V.; Karthikeyan, N. (Asian Journal of Chemistry, 2010)
Studies on properties of the isonitroso-β-diketones are conducted. Reactivity of coordinated ligands of bivalent quadridentate chelates of Ni(II) and Cu(II) is studied. Diazo coupling reactions on metal Schiff bases are conducted. Selective nature of the diazo coupling reactions is demonstrated by the isolation of monodiazo coupled products. To prove quasiaromaticity, iodination and α-naphthylisocyanation reactions are conducted on monoaryldiazo bivalent tetradentate β-ketoimine complexes of Ni(II) and Cu(II) and the products are characterised by analytical, magnetic, IR, NMR and ESR techniques.